2011
DOI: 10.1007/s10681-011-0388-z
|View full text |Cite
|
Sign up to set email alerts
|

Papaya ringspot virus resistance in Carica papaya via introgression from Vasconcellea quercifolia

Abstract: We report the first successful production of PRSV-P resistant backcross (BC) papaya plants following intergeneric hybridisation between C. papaya and a Vasconcellea species after 50 years of reports on unsuccessful attempts. This follows our previous reports of PRSV-P resistant F 1 hybrids developed by intergeneric hybridisation between C. papaya and V. quercifolia. One PRSV-P resistant BC 1 (BC 1 ) plant was produced after 114,839 seeds were dissected from 940 fruits. The seeds yielded 1,011 embryos and 733 g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
20
0
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(25 citation statements)
references
References 20 publications
(27 reference statements)
0
20
0
2
Order By: Relevance
“…A morphological synapomorphy supporting this relationship is a unilocular ovary, while the remaining Caricaceae have 5-locular ovaries. Breeding efforts for papaya improvement should include the four species now revealed as the closest relatives, rather than focusing only on the highland papayas in the genus Vasconcellea (Sawant, 1958;Drew et al, 1998;Siar et al, 2011). So far, studies on the biology of the herbaceous Caricaceae are restricted to an investigation on the cultivation of the lowland species Jarilla chocola (Willingham and White, 1976).…”
Section: The Closest Relatives Of Carica Papaya and The Region Of Thementioning
confidence: 99%
See 2 more Smart Citations
“…A morphological synapomorphy supporting this relationship is a unilocular ovary, while the remaining Caricaceae have 5-locular ovaries. Breeding efforts for papaya improvement should include the four species now revealed as the closest relatives, rather than focusing only on the highland papayas in the genus Vasconcellea (Sawant, 1958;Drew et al, 1998;Siar et al, 2011). So far, studies on the biology of the herbaceous Caricaceae are restricted to an investigation on the cultivation of the lowland species Jarilla chocola (Willingham and White, 1976).…”
Section: The Closest Relatives Of Carica Papaya and The Region Of Thementioning
confidence: 99%
“…Molecular data have revealed that the closest relative of papaya is a clade of four species in Mexico and Guatemala previously entirely neglected by ecologists and breeders . One of the main impediments for C. papaya production is the papaya ring spot virus, although some Vasconcellea are tolerant to the disease Siar et al 2011;. The lack of knowledge of the true closest relatives of papaya resulted in the assumption that the highland papayas (Vasconcellea species) are the best group to use in papaya improvement (Scheldeman et al 2011;.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…After mechanical inoculation with PRSV-P isolated in the Philippines, plantlets without symptoms (72.3% to 96.1%) under greenhouse conditions were recorded. After 18 months in the field, plants from the BC 4 backcross were analyzed using the ELISA technique but only 66% of them were resistant (Siar et al, 2011). In BC 3 plants, the ratio of resistant: susceptible segregants was 3:1, whereas in BC 4 plants two types of ratio were observed: 2:1 and 4:1.…”
Section: Introgresión De Genes De Resistencia a Virusmentioning
confidence: 99%
“…One way to do that is by using wide hybridization (Hajjar and Hodgkin 2007). However, attempts have been done since 1958 by Jimenez and Horovitz (1958) and Horowitz and Jimenez (1967) and the transference of resistance gene from wild to the cultivated papaya is not well succeeding unless embryo rescue technique is used (Magdalita et al 1996, Siar et al 2011.…”
mentioning
confidence: 99%